2017
DOI: 10.1080/09273972.2017.1391851
|View full text |Cite
|
Sign up to set email alerts
|

Third Cranial Nerve Palsy after a Chikungunya Virus Infection

Abstract: Chikungunya fever is a disease caused by a virus from the same family as dengue and Zika. It is endemic in several parts of the world and has recently spread to Latin America. We report the case of a patient, aged 58 years, from Rio de Janeiro, Brazil, who in 2013 developed an acute bilateral third cranial nerve palsy sparing the pupil. After extensive investigation, it was diagnosed as caused by chikungunya infection. The patient was treated with pulse therapy and after 5 months of the onset of the condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, the patient presented a partial acute extrinsic paralysis of the left third cranial nerve, spontaneously resolving in 7 days following a severe form of SARS-CoV-2. To our knowledge, third cranial nerve palsy has already been described with some viruses, suggesting some hypotheses [1][2][3][4]. SARS-CoV-2 is a neurotrophic virus that can induce encephalitis.…”
Section: Dear Sirsmentioning
confidence: 99%
“…Therefore, the patient presented a partial acute extrinsic paralysis of the left third cranial nerve, spontaneously resolving in 7 days following a severe form of SARS-CoV-2. To our knowledge, third cranial nerve palsy has already been described with some viruses, suggesting some hypotheses [1][2][3][4]. SARS-CoV-2 is a neurotrophic virus that can induce encephalitis.…”
Section: Dear Sirsmentioning
confidence: 99%
“…Indeed, the clinical features of cranial nerve palsies in childhood are affected by children’s ability to repair and regenerate after injury [ 8 ]. Other neurotropic viruses such as herpes (HSV, herpes zoster virus, EBV, CMV) and, chikungunya also can cause cranial nerve palsy [ 9 ]. Although the vast majority of children with COVID-19 have a favorable clinical course, pediatricians should be aware of the possibility of particular clinical manifestations such as Pediatric Multisystem Inflammatory Syndrome (PMIS) temporally associated with COVID-19, and now isolated cranial nerve palsy, which until then had been the prerogative of adults.…”
Section: Discussionmentioning
confidence: 99%
“…This virus causes the release of cytokines that have direct and indirect neurotoxic action. Techniques of immunohistochemistry have already demonstrated that infected neurons can undergo apoptosis [5].…”
Section: Dear Sirsmentioning
confidence: 99%